Black Seed (Nigella sativa) Extract Induce in vitro Proliferation and Differentiation of Rat Pancreatic and Bone Cells (EKSTRAK JINTAN HITAM (Nigela sativa) MENGINDUKSI PROLIFERASI DAN DIFERENSIASI SEL PANKREAS DAN SEL TULANG TIKUS SECARA IN VITRO) - Prasetyaningtyas, Wahono Esthi; Romadhon, Deny Putra; Susana, Fitri; Djuwita, Ita; Mohamad, Kusdiantoro (Jurnal Veteriner, 2016)
Black seed (Nigella sativa), a medicinal plant, widely used for treating various diseases, includingdiabetes mellitus and osteoporosis. This study examined the proliferation and differentiation of pancreaticand bone cells of rat cultured in vitro in medium supplemented with N. sativa extracts (NS). Pancreaticand bone cells were isolated from five days old rat and cultured in Dulbecco modified eagle mediumsupplemented without NS (0%, as control), and with NS (0.05% and 0.5%, as treatment groups) in 5% CO2incubator at 37oC for seven days and observed for cell population doubling time (PDT); proportion anddiameter of Langerhans islets, osteoblast, and osteocyte; and proportion of Langerhans islets containingb cell expressing insulin secretion. The pancreatic b cells were observed using dithizone staining, while thebone cells using alizarin red staining. The result showed that supplementation of NS significantly (p<0.05)decreased the PDT of pancreatic and bone cells, increased the proportion and diameter of Langerhansislets, increased the proportion of expression the b cell producing insulin, and increased the diameter ofosteoblast. In conclusion, the supplementation of NS in culture medium improved the proliferation anddifferentiation of pancreatic and bone cells in vitro.
Keywords: in vitro culture; Nigella sativa; osteoblast; osteocyte; pancreatic b cell